Performance Evaluation and Vendor Segmentation System Based on AHP and Kraljic Matrix to Improve Procurement Efficiency at Pt Pln (Persero) - Novananda, Chanygia; Partiwi, Sri Gunani (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to improve the vendor performance evaluation and segmentation system at PT PLN (Persero) using the Analytical Hierarchy Process (AHP) and Kraljic Matrix approaches. The current vendor performance evaluation system is considered suboptimal in providing holistic, objective, and integrated assessments across business units. Issues such as inconsistent use of subcriteria, subjective assessments, and the absence of vendor segmentation have resulted in inefficiencies in the procurement process. The study was conducted through literature reviews, internal documentation analysis, field observations, and focus group discussions (FGDs) with experts in the PLN environment. The proposed evaluation system consists of four main criteria: managerial, technical, administrative & financial, and safety, with a total of 14 subcriteria. Additionally, this research developed an AHP-based vendor evaluation form and designed vendor segmentation into four categories: routine, leverage, critical/bottleneck, and strategic. Simulations conducted on five PLN work units for one vendor showed improvements in consistency, efficiency, and objectivity of assessment, resulting in holistic evaluation outcomes and uniform segmentation. The system provides a foundation for vendor database integration, strengthens procurement governance, and supports risk and value-based decision-making in the procurement process.